Integration of ultrasound simulation to improve medical student knowledge and satisfaction on the obstetrics and gynecology clerkshipAJOG MFM at a Glance - Anthony Shanks, MD; Adrianna Darwish, DO; Myanna Cook, BA; Ivana Asencio, MD; Carrie Rouse, MD (Elsevier, 2023)
BACKGROUND: There has been increased use of ultrasound in contemporary medical education. Students tend to report a higher sense of satisfaction when ultrasound is incorporated into medical education, but little is known about whether its use leads to an improvement in medical knowledge acquisition independent of the ultrasound skill. In addition, there is no consensus among obstetrics and gynecology clerkships on the most effective way to incorporate ultrasound into the clerkship curriculum. OBJECTIVE: This project described a method to integrate ultrasound simulation into an obstetrics and gynecology clerkship curriculum. Our hypothesis was that the incorporation of ultrasound simulation in the obstetrics and gynecology clerkship curriculum will lead to an increase in standardized assessments of obstetrics and gynecology knowledge. STUDY DESIGN: A prepost study at a single institution with multiple methods design was employed. Of note, 10 high-yield pathology topics commonly tested on the Association of Professors of Gynecology and Obstetrics quizzes and National Board of Medical Examiners examinations were summarized into study sheets and associated with a representative ultrasound simulation module. All students were provided access to the summary sheets. Students with instruction in ultrasound simulation consisted of the postintervention group and were compared with students that did not have ultrasound simulation (preintervention group). Quiz and examination scores were compared between the groups. In addition, students who accessed the ultrasound simulator were given a survey at the end of their rotation to obtain qualitative information regarding satisfaction and the incorporation of ultrasound into the clerkship curriculum. RESULTS: There was no significant difference in quiz or examination scores between students who had access to the ultrasound simulation and those who did not. Most students found the integration of ultrasound simulation into the obstetrics and gynecology clerkship to be beneficial, to enhance their learning, to boost their confidence in ultrasound skills, and to be a potential substitute for clinical ultrasounds during the rotation. CONCLUSION: Integration of ultrasound simulation into obstetrics and gynecology clerkships and medical school education is understudied but can be a valuable educational tool. The incorporation of ultrasound into the medical education system is a topic of current studies. This study found that integration was viewed favorably by students, although integration was not associated with an improvement in medical knowledge measured via quiz and examination performance. Our research provided students with a standardized ultrasound education experience, which improved student satisfaction with the obstetrics and gynecology clerkship but did not correlate to increased demonstrated medical knowledge and understanding of examinations. Moving forward, student participants provided various suggestions on how we can continue to enrich medical students' education with the implementation of ultrasound.